Common "transmission block" in understanding cardiovascular physiology - Hwee-Ming Cheng; See-Ziau Hoe; Amira Abd Jamil (Wolters Kluwer Medknow Publications, 2017)
We obtained responses from 69 medical and 65 pharmacy students who had cardiovascular (CVS) physiology taught in the previous academic year. A real-time response exercise using an online game-based learning platform (Kahoot!) (https://getkahoot.com/) was conducted during a lecture class using true/false questions that cover certain core aspects of CVS physiology. Comments will be made on some of the common, incomplete understanding of CVS conceptual mechanisms. Some follow-up thoughts on our role as physiology educators in fine-tuning our teaching as we encounter persistent mistakes among our students' learning physiology.